Greenland, view of Kjerulf Fjord through to Dicksons Fjord annotated by Louise A. Boyd - Boyd, Louise Arner, 1887-1972 (1931)
August 2, 1931. Kjerulfs [Kjerulf] Fjord. Through to Dickson [Dicksons] Fjord. In background on left: Curry-comb Peak forming west side of Left Valley. In background on right; mountains forming north side of Right Valley and snow-patch on summit (extreme right) is turn of range to North, where it is seen forming western side of Main Valley, north of which it continues forming west side of Kjerulfs [Kjerulf] Fjord, ending with Riddarborgen at N.W. point of Kjerulfs [Kjerulf] Fjord. The lower part and base of these mountains are shown in photos 24-F-19; 24-F-20; 27-1-7; 27-1-8; 27-1-9. In foreground: Southern terminal of range of mts. [mountains] forming eastern side of Kjerulfs [Kjerulf] Fjord, including Main Valley and Left Valley. Photo taken at S.E. end of Left Valley, looking W.N.W. This is No 24 in pan C.